Are House Prices Rising too Fast in Hong Kong SAR? (IMF Working Papers; Working Paper ;, 2010)
Sharp increase in house prices in Hong Kong SAR in 2009-2010 has led to concerns of an emerging real estate bubble. According to our measure of price deviation from fundamentals, which should be taken as an early warning indicator of market exuberance, the current level of house prices in Hong Kong SAR does not seem to be significantly higher than would be justified by underlying fundamentals. Moreover, unlike advanced economies before 2007-8, deviation from fundamentals has not been persistent in Hong Kong.Going forward, low interest rate and improving growth prospects, as well as a tight supply, particularly in the mass market, means that house price growth will continue to be strong.This is the period in which vulnerability may be accumulating, and tight prudential standards and fiscal measures will be required to tame price inflation.